Rippin' it old-school - Bean, Raymond; Gibson, Ben (Las Vegas, NV : AmazonEncore, 2010)
Life has not been easy for Keith Emerson since he created a cure for the common fart as he deals with his parents claims that Keith turned his sister into a farting maniac, his best friends' teasing, his mentor's demands, and the pressure of developing a winning project for the science fair, but Keith receives some help from an unexpected source and learns a surprising lesson.
Booklist
Booklist, September 2010
4.5
3-6
3-6
Keywords: Schools -- Juvenile fiction; Science projects -- Juvenile fiction; Humorous stories; Schools -- Fiction; Science projects -- Fiction; Humorous fiction; School stories; Science projects -- Fiction; Humorous fiction